2023
DOI: 10.1186/s12906-023-04088-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and integrative health in Finland: a cross-sectional survey

Abstract: Background Population based studies have shown large differences in the estimated prevalence of complementary and integrative health (CIH) usage between studies. This is in part due to there being no golden standard definition for CIH. In Finland, an updated and internationally comparable study on the prevalence of CIH usage is needed. In the present study, a modified Finnish version of the International Questionnaire to Measure Use of Complementary and Alternative Medicine (I-CAM-QFI) was util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In regard to children's participation in research on complementary medicine, our findings indicate that female parents, in comparison to males and older parents, were more likely to express agreement. Women exhibit a greater inclination towards complementary and alternative medicine compared to men, as shown by numerous studies across a variety of diseases 21–25 . This trend appears to transcend borders and is observed in many countries worldwide, including the United States, 21,22 Malaysia, 23 Finland, 24 and Italy 26 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In regard to children's participation in research on complementary medicine, our findings indicate that female parents, in comparison to males and older parents, were more likely to express agreement. Women exhibit a greater inclination towards complementary and alternative medicine compared to men, as shown by numerous studies across a variety of diseases 21–25 . This trend appears to transcend borders and is observed in many countries worldwide, including the United States, 21,22 Malaysia, 23 Finland, 24 and Italy 26 …”
Section: Discussionmentioning
confidence: 97%
“…Women exhibit a greater inclination towards complementary and alternative medicine compared to men, as shown by numerous studies across a variety of diseases. [21][22][23][24][25] This trend appears to transcend borders and is observed in many countries worldwide, including the United States, 21,22 Malaysia, 23 Finland, 24 and Italy. 26 Our study revealed a noteworthy correlation between patients designating their gastroenterologist as their primary source of knowledge about IBD and its treatment, and a heightened willingness to participate in genetics and nutrition studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a part of a larger Finnish CIH research project. More details on sampling and recruitment are reported elsewhere 10 .…”
Section: Sampling and Recruitmentmentioning
confidence: 99%
“…The most commonly reported reasons for the use of CIH are the perceived bene ts and safety of CIH, and dissatisfaction with conventional medicine 6 . Reported bene ts include management of pain 7 , perceived improvement of physical and emotional health and well-being and quality of life 6,8 , as well as CIH being reported by users as helpful 9,10 . The use of CIH has been attempted to be explained by having value t with CIH use 11 and by beliefs in magical concepts regarding health 12 , or holistic health and healing beliefs 13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation